Atypical IκB Bcl3 enhances the generation of the NF-κB p52 homodimer - Pan, Wenfei; Deng, Limei; Wang, Haitao; Wang, Vivien Ya-Fan (Frontiers in Cell and Developmental Biology, 2022)
The NF-κB family of dimeric transcription factors regulate diverse biological functions. Their cellular expression profiles differ which leads to different concentrations in different cell/tissue types. While the activation mechanisms of different NF-κB dimers have been widely investigated, there is limited information on specific NF-κB dimers formation. The NF-κB p52:p52 homodimer regulates an important subset of target genes in cancer cells; however, the molecular mechanism of the generation of this specific homodimer remains unclear. Our study has revealed that the atypical IκB protein, Bcl3, plays an essential role in enhancing the p52:p52 homodimer formation which is an unique mechanism to p52 within the NF-κB family. p52 was shown to heterodimerize with four other NF-κB subunits (RelA, RelB, cRel and p50); and all heterodimers, except p52:p50, are significantly more stable than the p52:p52 homodimer. Bcl3 is able to compete with all other NF-κB subunits in cells for efficient p52:p52 homodimer formation which consequently leads to the upregulation of taget genes that are involved in cell proliferation, migration and inflammation which explain why aberrant activation of Bcl3 and p52 leads to cancer.